Congenital pyloric mucosal fold resulting in an antral valve outflow obstruction in a bull terrier. (21st December 2012) - Pazzi, P.; Hartman, M. J.; Schoeman, J. P.
Abstract : An under‐sized three‐month‐old female bull terrier was referred with a history of regurgitation since three days of age. Thoracic radiographs were unremarkable, while abdominal radiographs showed a distended stomach, despite a 12 hour fast. Abdominal ultrasonography revealed gastric outflow obstruction of unclear aetiology. Coeliotomy was performed, during which an excessive mucosal fold at the pyloric antrum was excised. Histopathology of the pyloric fold revealed mild oedema and fibrosis of the mucosal tissue. The dog made a complete recovery, with resolution of regurgitation and grew to within the expected breed size. In the authors' opinion, this is the first canine report of congenital antral mucosal valve resulting in gastric outflow obstruction, and only the second report in any species.